2019
DOI: 10.1038/s41598-019-53837-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Vegetation Coverage and Climate Environment on Soil Organic Carbon in the Qilian Mountains

Abstract: Studying the spatial distribution pattern of soil organic carbon and its influencing factors is essential for understanding the carbon cycle in terrestrial ecosystems. Soil samples from four active layers of typical vegetation types (Populus, subalpine shrubs, Picea crassifolia Kom, and alpine meadow) in the upper reaches of Shiyang River basin in the Qilian Mountains were collected to determine the soil organic carbon content and physicochemical properties. The results show the following: (1) There are signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…Taking the Xiying River Basin as an example, seasonal frozen soil is generally developed in the upstream river source area, and alpine meadow is a typical vegetation type in the frozen soil area. In addition, Wan et al's study on SOC concentration in the Xiying River Basin showed that the SOC concentration was the highest under the alpine meadow planting in the upstream permafrost area (Wan et al, 2019), which corresponds to the river documented concentration at the sampling point (M4) in the river source area of this study.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…Taking the Xiying River Basin as an example, seasonal frozen soil is generally developed in the upstream river source area, and alpine meadow is a typical vegetation type in the frozen soil area. In addition, Wan et al's study on SOC concentration in the Xiying River Basin showed that the SOC concentration was the highest under the alpine meadow planting in the upstream permafrost area (Wan et al, 2019), which corresponds to the river documented concentration at the sampling point (M4) in the river source area of this study.…”
Section: Discussionmentioning
confidence: 55%
“…In this study, it was found that there is a significant positive correlation between the organic carbon content of the river basin and the DOC concentration of the river (Figure 6). In other words, rivers that flow through areas with higher SOC density usually have higher DOC concentra- Basin showed that the SOC concentration was the highest under the alpine meadow planting in the upstream permafrost area (Wan et al, 2019), which corresponds to the river documented concentration at the sampling point (M4) in the river source area of this study.…”
Section: Influence Of Seasonal Frozen Soil Changes On River Docmentioning
confidence: 56%
See 3 more Smart Citations